Testing the dynamic balance and proprioception in team a romanian ski jumping athletes - Balint, G.; Spulber, F. (Gymnasium - Scientific Journal of Education, Sports and Health, 2011)
In the analysis meeting of the Ski jumping Technical Board regarding the activity of national teams in the winter season of 2009-2010, were brought up certain inconveniences that appeared during the training program, and manifest themselves negatively during competitions. After analyzing these inconveniences, we suggested certain specific activities for improving the results. The subjects of this research were the athletes in the Romanian team A of ski jumping. We think it is necessary that the suggestions we made in this paper should become permanent, without intervening on the plan of the instruction process, and we can say that these results, as well as the new suggested action means will improve the quality of the instruction process in our athletes.